2004
DOI: 10.17848/wp04-108
|View full text |Cite
|
Sign up to set email alerts
|

The Wage Effects of Schooling under Socialism and in Transition: Evidence from Romania, 1950-2000

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…For more analysis of the ILO categories in Romanian LFS data, with comparisons to Estonia and Russia, see Brown et al (2006). 6 Andren et al Andren et al (2005) study the changing impact of education on earnings in Romania from 1950 to 2000. See also Earle and Pauna (1998).…”
Section: Endnotesmentioning
confidence: 99%
“…For more analysis of the ILO categories in Romanian LFS data, with comparisons to Estonia and Russia, see Brown et al (2006). 6 Andren et al Andren et al (2005) study the changing impact of education on earnings in Romania from 1950 to 2000. See also Earle and Pauna (1998).…”
Section: Endnotesmentioning
confidence: 99%
“…The increase in wage inequality that started during the transition years and continued thereafter had been explained in the literature by factors such as the improved quality of the workforce due to sharp increase of enrolments in the higher education after 1989 (Skoufi as, 2003). In the same register, Andrén et al (2005) assessed the wage impact of schooling for Romanian workers, comparing the central planning period to the transition years, and found that the schooling wage premium, which was low under central planning, become more than double by 2000. Since the early 1990s, wages were set at the fi rm level, in better accordance to the employees' skills, thus producing a sizeable increase in wage inequality.…”
Section: Regional Wage Differentials and Wage Convergencementioning
confidence: 99%
“…We also know that returns to education (i.e. the extent to which a person's wage depends on their total years of schooling) in Romania have increased significantly since the end of socialism, as schooling has become more valuable (Andrén, Earle, and Săpătoru 2005). Nevertheless, clear findings about class production and reproduction remain elusive (Tomescu-Dubrow 2006).…”
Section: Social Stratificationmentioning
confidence: 99%